2019
DOI: 10.1056/nejmoa1810642
|View full text |Cite
|
Sign up to set email alerts
|

Patient Safety Outcomes under Flexible and Standard Resident Duty-Hour Rules

Abstract: BACKGROUND Concern persists that extended shifts in medical residency programs may adversely affect patient safety. METHODS We conducted a cluster-randomized noninferiority trial in 63 internal-medicine residency programs during the 2015–2016 academic year. Programs underwent randomization to a group with standard duty hours, as adopted by the Accreditation Council for Graduate Medical Education (ACGME) in July 2011, or to a group with more flexible duty-hour rules that did not specify limits on shift length… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
62
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(67 citation statements)
references
References 20 publications
2
62
1
2
Order By: Relevance
“…The potential impact of relaxing duty hour restrictions was assessed in the Individualized Comparative Effectiveness of Models Optimizing Patient Safety and Resident Education (iCOMPARE) trial, which recently demonstrated that chronic sleep loss and sleepiness were similar among interns in flexible programs and standard programs 44 . Further, no detriment to patient safety outcomes was observed 45 . However, by leveraging current technological advances of multisensory consumer sleep trackers and digital, momentary mood assessments, we were able to detail more granular relationships between sleep, depression, and daily mood which reveals the relevance of sleep regularity for optimal mental health in interns.…”
Section: Discussionmentioning
confidence: 92%
“…The potential impact of relaxing duty hour restrictions was assessed in the Individualized Comparative Effectiveness of Models Optimizing Patient Safety and Resident Education (iCOMPARE) trial, which recently demonstrated that chronic sleep loss and sleepiness were similar among interns in flexible programs and standard programs 44 . Further, no detriment to patient safety outcomes was observed 45 . However, by leveraging current technological advances of multisensory consumer sleep trackers and digital, momentary mood assessments, we were able to detail more granular relationships between sleep, depression, and daily mood which reveals the relevance of sleep regularity for optimal mental health in interns.…”
Section: Discussionmentioning
confidence: 92%
“…Although the primary outcome of the iCOMPARE trial focused on patient safety, as reported in a companion article in this issue of the Journal , 20 the trial was designed to simultaneously assess the effects on educational experiences, which were reported previously, 21 and on the sleep and alertness of interns, which we report here. The latter aim was to establish whether sleep and alertness among interns in flexible programs were noninferior to those among interns in standard programs according to pre-specified noninferiority margins.…”
mentioning
confidence: 99%
“…To address the duty-hour question, two trials have recently been performed on surgery and internal medicine residents. 8,9 The trials were designed as ‘non-inferiority’ studies, a low bar in which longer shifts need only show not substantially worse patient mortality than shorter shifts. ‘Shorter’ shifts (up to 16 – 28 hours) are still longer than in the majority of professional jobs, yet they were disfavoured from the start by the non-inferiority design.…”
Section: Panglossian Fallacy 2: Arduous Training and Examination Are mentioning
confidence: 99%